(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
The article explores the presence and influence of the puppet theater Kasperltheater in Santa Catarina, as part of the German cultural heritage brought by immigrants since the 19th century. Originating in Germany, Kasperl is a central character in the country’s popular puppet theater, portrayed both as a hand puppet and a string marionette. The text highlights the role of the Hohnsteiner Handpuppenspiele company in popularizing Kasperl and spreading it in Brazil, particularly in German-descendant communities in Santa Catarina. Through historical accounts, such as those by Margarethe Schlünzen ("Móin-Móin") and Hildor Emmel, the article demonstrates how Kasperltheater was integrated into daily life, education, and local traditions, resurfacing in the 21st century through cultural and artistic initiatives. The play Kasperl e a Cerveja do Papa (Kasperl and the Pope’s Beer) by Trip Teatro exemplifies the contemporary adaptation of this tradition, bridging past and present. The study reveals Kasperl’s importance as a symbol of cultural resistance and its relevance to Santa Catarina’s identity.